Maintaining The Role Of Loyalty During Transitions: Mediating Job Satisfaction In The Relationship Between Career Development And Turnover Intention In The Natural Gas Industry - Rizal Muttaqien; Rima Rahmayanti (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to analyze the influence of career development on turnover intention with job satisfaction as a mediating variable among employees of PT Perusahaan Gas Negara Tbk. SOR II. The background of this study is based on the increasing employee turnover intention which is correlated with limited access to managerial training, strict promotion processes, and low perceptions of fairness in career development after the company merger. This study uses a quantitative approach with a descriptive verification design. Data collection techniques were carried out through questionnaires and interviews with 88 permanent respondents. The results of the analysis indicate that career development has a direct and significant effect on job satisfaction, and simultaneously influences turnover intention, both directly and indirectly. Job satisfaction is proven to be a significant mediator in the relationship between career development and turnover intention, strengthening the strategic role of this variable in managing human resource retention. These findings emphasize the importance of establishing a fair, measurable, and transparent career development system to increase job satisfaction and reduce employee turnover intention. This study provides an empirical contribution to the literature on human resource management in the energy sector, particularly in the context of the national natural gas industry which is still rarely studied in depth.